Powerful knowledge, transposition/transformation and ICT: an empirical study across school subjects in primary education - Ramírez, Elena; Martín-Domínguez, Jorge; Rodríguez, Inés; Pérez González, Alicia; Martín-Sánchez, Inmaculada (Cambridge journal of education, 2023)
This article presents a study that analyses the types of activity used to teach the curriculum in primary education, and the use made accordingly of digital and analogue resources. The research's purpose was to discover whether there are any differentiated patterns of activity in the teaching of these subjects, and whether they are linked to the use of ICT/non-ICT resources. A multiple case study was conducted with 10 primary teachers, with three schooldays being recorded over the 2018-2019 school year, which provided 132 hours of recordings. The research design involved the use of mixed methods. The results reveal a differentiated use of patterns of activity linked to the subjects that make up the curriculum in primary education, as well as a differentiated use of ICT and non-ICT resources when teaching these subjects. The study includes the need to investigate the process of transforming/transposing the academic content into effective classroom teaching practices.